Quantifying the contribution of zoos and aquariums to peer-reviewed scientific research - Tse-Lynn Loh; Eric R. Larson; Solomon R. David; Lesley S. de Souza; Rebecca Gericke; Mary Gryzbek; Andrew S. Kough; Philip W. Willink; Charles R. Knapp (Canadian Science Publishing, 2019)
Modern zoos and aquariums aspire to contribute significantly to biodiversity conservation and research. For example, conservation research is a key accreditation criterion of the Association of Zoos and Aquariums (AZA). However, no studies to date have quantified this contribution. We assessed the research productivity of 228 AZA members using scientific publications indexed in the ISI Web of Science (WoS) database between 1993 and 2013 (inclusive). AZA members published 5175 peer-reviewed manuscripts over this period, with publication output increasing over time. Most publications were in the zoology and veterinary science subject areas, and articles classified as "biodiversity conservation" by WoS averaged 7% of total publications annually. From regression analyses, AZA organizations with larger financial assets generally published more, but research-affiliated mission statements were also associated with increased publication output. A strong publication record indicates expertise and expands scientific knowledge, enhancing organizational credibility. Institutions aspiring for higher research productivity likely require a dedicated research focus and adequate institutional support through research funding and staffing. We recommend future work build on our results by exploring links between zoo and aquarium research productivity and conservation outcomes or uptake.